Amateurization and professionalization from the perspective of missionary effectiveness. (April 2014) - Plake, John Farquhar
Missionary effectiveness is found at the confluence of divine calling, human need, and missionary ability. Missionaries are ineffective when their abilities—including spiritual formation, missiological education, and ministry development—are inappropriate for the context to which God has called them as ambassadors. Great ability without divine calling is professionalism, and inadequate ability to respond to the divine calling and human need is amateurism. Since short-term missionaries possess limited abilities, they may serve appropriately in limited contexts. However, all missionaries can and should grow. As missionary ability increases, so do the possibilities for appropriate engagement in God's mission of redemption.